Acute bacterial gastroenteritis: a study of adult patients with positive stool cultures treated in the emergency department. Issue 4 (1st July 2003) - Chan, S S W; Ng, K C; Lyon, D J; Cheung, W L; Cheng, A F B; Rainer, T H
Abstract : Objectives: To investigate the presenting clinical features of acute bacterial gastroenteritis in adult patients treated as outpatients in the emergency department (ED), and the pathogens responsible in this setting and population; and to identify the frequency with which positive stool culture result changes management. Method: This was a retrospective study of all patients who attended the accident and emergency department of an university affiliated hospital in Hong Kong over a 12 month period, who satisfied the following inclusion criteria: (a) age ⩾16, (b) presented with acute gastroenteritis, (c) treated as outpatients with or without observation, and (d) had positive stool cultures. Results: One hundred and thirty patients were included. Pathogens identified were Vibrio parahaemolyticus (42.3%), Samonella spp (34.6%), Plesiomonas spp (9.2%), Campylobacter spp (6.9%), Aeromonas spp (6.9%), and Shigella spp (6.2%). Mean highest body temperature was 37.5°C (95% confidence intervals (CI) 37.3 to 37.6). Bloody diarrhoea was present in 14 patients (10.8%). Mean duration of diarrhoea, from onset to the completion of stay in ED, was 2.2 days (95% CI 1.7 to 2.7). Likewise, mean duration of abdominal pain was 1.8 days (95% CI 1.5 to 2.1). Mean number of unformed stools per day was 9.3 (95% CI 8.3 to 10.3). Change of management, subsequent to the availability of positive stool culture results, was not required in 115 (88.5%) patients. Ciprofloxacin resistance occurred in eight (6.2%) cases, and seven of nine campylobacter isolates. Campylobacter positive patients had a significantly longer duration of abdominal pain (p=0.0236) and were less likely to be dehydrated (p=0.0103). Conclusions: Most patients with bacterial gastroenteritis do not present with high fever, bloody diarrhoea, or persistent diarrhoea, but generally have quite severe diarrhoea. Stool cultures do not change management for most patients. Vibrio parahaemolyticus is the commonest bacterial pathogen identified.